Changes in wood-water relations in acetylated wood over the course of Rhodonia placenta brown rot decay - Belt, Tiina; Altgen, Michael (Springer Science and Business Media LLC, 2025)
Acetylation greatly increases the decay resistance of wood, but even highly acetylated wood can be degraded by fungi if given sufficient time. This study investigated the degradation of acetylated wood by the brown rot fungus Rhodonia placenta, aiming to understand the fungal-induced changes in wood-water relations that are associated with decay. Acetylated samples as well as unacetylated references were exposed to R. placenta in a stacked-sample decay test to generate samples in different stages of decay. The decayed samples were used to investigate changes in acetyl content, water vapour sorption, and maximum cell wall moisture content as measured by solute exclusion. R. placenta caused high mass losses in acetylated wood, but preferential deacetylation was seen only in highly acetylated samples in the early stages of decay. Acetylated samples showed increased hygroscopicity in sorption measurements as a result of R. placenta degradation, particularly at high relative humidity in desorption from the undried decaying state. The increase was very strong in the highly acetylated samples and took place at low mass losses, indicating that it may be at least partially related to the deacetylation of the wood material. Degradation also increased maximum cell wall moisture content, but the increase was stronger in the references than the acetylated samples, suggesting that the acetyl groups remaining in the samples continue to provide a cell wall bulking effect.
Keywords: durability; dynamic vapour sorption; hygroscopicity; moisture; solute exclusion; wood modification; acetylation; anhydride; brown rot; decay